Research on the interactive effects of parenting advertising under the Sustainable Development Goals (SDGs) - Ting, Deng; Ibrahim, Rahinah (Brazilian Journals, 2024)
Objective: The objective of this study is to investigate the different effects of advertising interactive experiences, and explore effective advertising interactive methods, to provide effective parenting advertising training for abusive parents. Theoretical Framework: Refers to the multi-sensory advertising interaction model based on the studies before, such as the AIEDA tourism advertising effects model, schema congruence theory, and a spiral brand experience concept. Method: This study conducted the distinct "Systematic Literature Review Synthesis Process", a stand-alone literature review typology that helps make sense of a chosen body of current literature and helps determine the theoretical framework at the early stages of research ideation. Results and Discussion: The results revealed that visual, auditory, and multi-sensory interactions all have different elements and characteristics and could cause different levels of attention, memory, and emotions for audiences. Research Implications: The results are expected to guide the development of a theoretical framework for combining advertising and user experience interaction. Originality/Value: The research helps to identify interactive sensory experience characteristics in advertisements, guide the effective dissemination of parenting public service advertisements, and create a happier family atmosphere for children, to promote SDG 3 on ensuring healthy lifestyles and promoting the well-being of people of all ages.